Child nutrition and gender relations: Case study of dairy goat and improved root crop project in Mvomero and Kongwa district, Tanzania - Meena, P.H. (Sokoine University of Agriculture, 2013)
The nutritional status of children below five years of age is a sensitive indicator of a country’s health status as well as economic condition. This descriptive cross–sectional study aimed at examining child nutritional status and gender relations among dairy goat and improved root crop project beneficiaries in Mvomero and Kongwa Districts in Tanzania. A total of 107 households were purposively selected whereby 107 adult respondents and 74 children below five years of age were involved. A structured questionnaire was used to determine dietary pattern of the households and gender relations while anthropometric measurements were taken to assess the nutritional status of the children below five years of age. Data were analyzed to obtain frequencies, percentages, means and standard deviation. Chi square test and ANOVA were used to assess association between child nutritional status and the independent variables considered in the study. Results showed that the mean age of the children was 27.8 months and of adult respondents was 38.5 years. The mean household size was 5.9 people. Majority of the respondents were primarily farmers, 35.5% in Kongwa and 35.5% in Mvomero District. There were more male children 55.4% than female children 44.6%. The prevalence of stunting was higher in Kongwa District (67.3%) than Mvomero district (33.3%). Stunting was high in children aged 12 to 23 months. 36.1% of children were introduced complementary feeding at early age of below six months. In Kongwa and Mvomero Districts, 56.1% and 27.4% of mothers respectively used maize porridge as complementary food. Staple food was stiff porridge and vegetables. Protein foods were rarely consumed while fruits were seldom consumed. Resource ownership, control and decision making were done by men. It is recommended that, training on nutritional education and importance of women contribution on decision making, control and ownership of resources should be provided.